How Much Is It Worth to Protect Sensitive Products with Tariff-Rate Quotas?—A Korean Case - 임송수 (한국농촌경제연구원, 2013)
The tariff-rate quota (TRQ) system is a hybrid import regime that conveys both tariff- and quota-like characteristics. Established by the tariffication process during the Uruguay Round, TRQs harmonize the needs for improved market access and protection from import surges. This paper aims to identify economic and policy consequences from TRQ implementation and to test whether the trade-off between formula tariff cuts and quota expansion is adequate and thus is beneficial to the protection of declared sensitive products. Using Korea’s case of soybean imports, this paper illuminates the importance of quota administration in terms of mark-ups, economic rents and the state-trading enterprises (STEs). Application of a one-product partial equilibrium model to Korea’s soybean market suggests that it would be better for Korea to designate soybeans as a category of sensitive products. The derived quota equivalents under the option of sensitive products turn out to be smaller than otherwise. Examination of quota equivalents for formula tariff cuts indicates different proportionality or trade-offs among options. Finally, it concludes with potential areas to improve the TRQ administration under the WTO modalities.
Keywords: tariff-rate quota; sensitive product; tariff equivalent; quota equivalent; soybeans; tariff-rate quota; sensitive product; tariff equivalent; quota equivalent; soybeans